Large Payload Streaming Database Sort and Projection on FPGAs - Sukhwani, Bharat; Thoennes, Mathew; Min, Hong; Dube, Parijat; Brezzo, Bernard; Asaad, Sameh; Dillenberger, Donna (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2013)
In recent years, real-time analytics has seen widespread adoption in the business world. While it provides useful business insights and improved market responsiveness, it also adds a computational burden to traditional online transaction processing (OLTP) systems. Analytics queries involve complex database operations such as sort, aggregation, and join that consume significant computational resources, and, when executed on the same system, may affect the performance of OLTP queries. In this paper, we try to address this issue by accelerating two such database operations, namely, projection and sort, using a field programmable gate array (FPGA). Our prototype is implemented on an Alter a Stratix V FPGA and achieves an order of magnitude speedup in the sort operation compared to baseline software. Furthermore, our prototype implements projection in parallel with other query operations on FPGA, thus completely eliminating the cost of projection without consuming any extra cycles on the FPGA. FPGA accelerated sort and projection have been integrated with our previous work on accelerating other query operations [1], making our analytics acceleration prototype on FPGA applicable to a wider variety of queries.